2022
DOI: 10.3389/fbioe.2022.1042867
|View full text |Cite
|
Sign up to set email alerts
|

The uncommon function and mechanism of the common enzyme glyceraldehyde-3-phosphate dehydrogenase in the metamorphosis of Helicoverpa armigera

Abstract: Glyceraldehyde-3-phosphate dehydrogenase (GAPDH), a key enzyme in glycolysis, is commonly used as an internal reference gene in humans, mice, and insects. However, the function of GAPDH in insect development, especially in metamorphosis, has not been reported. In the present study, Helicoverpa armigera and Spodoptera frugiperda ovarian cell lines (Sf9 cells) were used as materials to study the function and molecular mechanism of GAPDH in larval metamorphosis. The results showed that HaGAPDH was more closely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is a key enzyme participating in glycolysis and glucose metabolism ( Zhao et al, 2022 ). Similar to our results, the instability of GAPDH expression has reported in Ophraella communa ( Zhang et al, 2020 ) P. brassicae ( Ma et al, 2021 ) and Colaphellus bowringi ( Tan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is a key enzyme participating in glycolysis and glucose metabolism ( Zhao et al, 2022 ). Similar to our results, the instability of GAPDH expression has reported in Ophraella communa ( Zhang et al, 2020 ) P. brassicae ( Ma et al, 2021 ) and Colaphellus bowringi ( Tan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present studies reported GADPH among the top five reference genes in the fourth and fifth instar, adult males and females (Table 1). GADPH plays a vital role in forming membranes, microtubules, phosphotransferase, and kinase reactions [39]. The expression of this gene was also documented to be highly stable in the various development stages of S. litura larvae under temperature stress [40] as well as in the bacteria-infected bee Apis mellifera [41].…”
Section: Reference Genes Analysismentioning
confidence: 98%